Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.5 Derivatives of Trigonometric Functions - 3.5 Exercises: 17

Answer

$y' = cos (x) - sin (x)$

Work Step by Step

$y = sin (x) + cos (x)$ $y' = (sin (x) + cos (x))' = (sin (x))' + (cos (x))'$ $(sin (x))' = cos(x)$ $(cos (x))' = - sin(x)$ Therefore $y' = (sin (x) + cos (x))' = (sin (x))' + (cos (x))' = cos (x) - sin (x)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.